1969
DOI: 10.21273/jashs.94.4.400
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 2-Chloroethanephosphonic Acid (Ethrel) on the Sex Expression and Yields of Cucumis sativus1

Abstract: The effect of 2-chloroethanepliosphonic acid (ethrel) on the sex expression of pickling cucumbers was studied. Tests to determine concentrations, effect on sex expression, and yield potential were conducted in greenhouse and field situations. As many as 19 successive pistillate nodes were observed for the treated monoecious cultivar ‘SC 23’. The most effective concentrations of ethrel were 120, 180 and 240 ppm for these studies. These rates in single or multiple application resulted in the greatest number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
5
0

Year Published

1970
1970
1994
1994

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Interestingly, 2,3,5-triiodobenzoic acid (TIBA), which inhibits auxin transport (3,4,6), was reported to increase the femaleness of 2 cucumber cultivars (14). McMurray and Miller (8,9) and others (1,5,11,12) have reported that the femaleness of cucumbers and squash was increased by application of 2-chloroethylphosphonic acid (Ethrel), a substance which produces ethylene upon decomposition (13). Here we report greenhouse findings from treatment of cucumbers, cv.…”
mentioning
confidence: 82%
“…Interestingly, 2,3,5-triiodobenzoic acid (TIBA), which inhibits auxin transport (3,4,6), was reported to increase the femaleness of 2 cucumber cultivars (14). McMurray and Miller (8,9) and others (1,5,11,12) have reported that the femaleness of cucumbers and squash was increased by application of 2-chloroethylphosphonic acid (Ethrel), a substance which produces ethylene upon decomposition (13). Here we report greenhouse findings from treatment of cucumbers, cv.…”
mentioning
confidence: 82%
“…Rudich et al (27) suggests that the observed effects of auxin on sex expression result from auxin-induced ethylene formation. Recently, ethylene has been established as an endogenous regulator of sex expression of Cucumis melo L. (3), and ethephon3 [an ethylene releasing compounds (5,29)] has been used to enhance femaleness in monoecious cucurbits (4,14,17,25,27,28). Our objective was to determine whether ethephon might induce pistillate flowers on an androecious phenotype of cucumber and to obtain seed for further experimentation.…”
mentioning
confidence: 99%
“…Recently, a new ethylene-releasing growth regulator, ethe phon, has been explored for its ability to regulate sex expression in cucurbits. Foliar applications of this compound have been demonstrated to inhibit staminate flower development and to promote pistillate flowering in cucumber (11,12,19) and squash (10,20). This effect is similar to but much more dramatic than that reported for auxin promotion of pistillate flowering in cucurbits (13,16,23).…”
mentioning
confidence: 99%